HUBUNGAN PAPARAN ROKOK, KONSUMSI TEH, JARAK KELAHIRAN DENGAN ANEMIA IBU HAMIL DI BPM KERTAPATI - M. Sri Sundari; Minarti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
fulfill its function to carry sufficient amounts of oxygen to peripheral tissue. The prevalence ofanemia in pregnant women in Asia is 48.2%, while for Southeast Asia itself it is 97.8%. Purpose :Of this study is to find out whether there is a relationship between exposure to cigarette smoke,frequency of tea consumption and distance of birth with anemia status in pregnant women in BPMSundari Kertapati in 2019. Method : This research uses analytical survey research method withcross sectional research design. Sampling was done using random sampling obtained as many as81 pregnant women. The instrument used was a questionnaire using the chi square test.Results :Showed that there was a significant relationship between exposure to cigarette smoke to anemiastatus with p = 0.007, there was no significant relationship between tea consumption and anemiastatus with p = 0.399, there was a significant relationship between birth distance against anemiastatus with p = 0.020. Suggestion : the role of health workers in providing counseling to pregnantwomen and husbands about the dangers of cigarette smoke and their effects on pregnancy is verynecessary, as well as the frequency of tea that should not be consumed every day.